Pengaruh Reformasi Perpajakan terhadap Kepatuhan Wajib Pajak di Indonesia - Indawati, Yana; Anggriawan, Teddy Prima; Sakti, Pusaka Bintang (LPPM Universitas Ekasakti Padang, 2024)
The purpose of this study is to investigate the impact of tax reform on the degree of taxpayer compliance in Indonesia. Using normative juridical methodologies, this paper examines Indonesia's most recent legislation and tax policies. The primary focus is on tax system modifications, which include administrative features, tax rates, and reporting procedures. Tax compliance data has been examined before and after the adoption of tax reform. According to the findings of the study, tax reform has a considerable impact on improving the Voluntary Complience. This is especially noticeable when the tax administration process is made more efficient and procedures are simplified. This study also noted several issues, including the need to raise tax awareness and strengthen the tax enforcement system. This study provides recommendations for strengthening tax reform methods to maximize tax revenues and taxpayer compliance in Indonesia.